The Role of the Indonesian Christian Student Movement on Political Life Medan City in 1965-1998 - Sitorus*, Friska Bunga Aulina; Perangin-angin, Elsima br; Sibarani, Natal; Pungki, Rina (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to explore the role of GMKI (Indonesian Christian Student Movement) in the political life of Medan City in 1965. This study describes the role of GMKI (Indonesian Christian Student Movement) and analyzes GMKI (Indonesian Christian Student Movement) in the political life of the Indonesian nation. The method used in this study is a qualitative method, with a descriptive approach. Data collection techniques were carried out using open observation guidelines, in-depth interviews, and documentation studies. The result of the research is that GMKI (Indonesian Christian Student Movement) is an important organization that has taken part in every activity of the Indonesian nation even before Indonesia proclaimed its independence. GMKI (Indonesian Christian Student Movement) has been established since 1927 and is still active, not only in the spiritual world, but also in the political world of Medan City.